Dissociable deficits in the decision-making cognition of chronic amphetamine abusers, opiate abusers, patients with focal damage to prefrontal cortex, and tryptophan-depleted normal volunteers: evidence for monoaminergic mechanisms. - Rogers, R; Everitt, B; Baldacchino, A; Blackshaw, A; Swainson, R; Wynne, K; Baker, N; Hunter, J; Carthy, T; Booker, E; London, M; Deakin, J; et al. (1999)
We used a novel computerized decision-making task to compare the decision-making behavior of chronic amphetamine abusers, chronic opiate abusers, and patients with focal lesions of orbital prefrontal cortex (PFC) or dorsolateral/medial PFC. We also assessed the effects of reducing central 5-hydroxytryptamine (5-HT) activity using a tryptophan-depleting amino acid drink in normal volunteers. Chronic amphetamine abusers showed suboptimal decisions (correlated with years of abuse), and deliberated for significantly longer before making their choices. The opiate abusers exhibited only the second of these behavioral changes. Importantly, both sub-optimal choices and increased deliberation times were evident in the patients with damage to orbitofrontal PFC but not other sectors of PFC. Qualitatively, the performance of the subjects with lowered plasma tryptophan was similar to that associated with amphetamine abuse, consistent with recent reports of depleted 5-HT in the orbital regions of PFC of methamphetamine abusers. Overall, these data suggest that chronic amphetamine abusers show similar decision-making deficits to those seen after focal damage to orbitofrontal PFC. These deficits may reflect altered neuromodulation of the orbitofrontal PFC and interconnected limbic-striatal systems by both the ascending 5-HT and mesocortical dopamine (DA) projections.